Subsidy for households to promote the adoption of more efficient and less polluting wood burning technologies: a numerical simulation for the case of Temuco and Padre Las Casas - Gómez, Walter; Yep, Sue; Chávez, Carlos (Estudios de Economía, 2013)
We study the effect of a household subsidy to induce the adoption of more efficient and less polluting wood combustion technologies. We compare, through numerical simulations, several subsidy designs with respect to the impact on aggregate emissions, costs, and cost-effectiveness indicators. Two variables that turn out to be important for the performance of a subsidy program are the remaining time that an existing equipment can be used and the access of the households to credit to fund the co-payment of the equipment. We observe that for different regulatory designs and/or different cost analysis, the performance of a subsidy program based on the cost-effectiveness analysis differs.